Anaerobic Digestion of Cattle Manure Contaminated with an Antibiotic Mixture: A Nature-Based Solution for Environmental Management - Giulia Massini; Anna Barra Caracciolo; Jasmin Rauseo; Francesca Spataro; Giulia Scordo; Luisa Patrolecco; Gian Luigi Garbini; Andrea Visca; Paola Grenni; Ludovica Rolando; Valentina Mazzurco Miritana (Land)
Anaerobic digestion (AD) is a waste-to-energy strategy that leverages natural microbiological processes. It is increasingly used in farms to treat manure, resulting in biogas for energy production and digestate as fertiliser. However, animal manure often contains antibiotic (AB) residues, raising concerns about their impact on AD efficiency and their potential spread through digestate use. This multidisciplinary study evaluated the effects of an AB mixture (enrofloxacin, ciprofloxacin and sulfamethoxazole) on CH4 production, microbial community (Fungi, Bacteria and Archaea) dynamics and antibiotic resistance gene (ARG) presence. The experiment used a cattle manure/digestate ratio of 1:35, typical of real digesters, with AB concentrations set at low (2.5 mg kg−1 each) and high (7.5 mg kg−1 each) levels. The ABs affected cumulative CH4 production (ranging from 5939 to 6464 mL) only at the highest concentration. After 51 days, sulfamethoxazole reached residual levels, while enrofloxacin and ciprofloxacin were only partially degraded (<50%), but ARGs were significantly reduced. The microbial community, particularly prokaryotes, exhibited resilience, maintaining efficient CH4 production. Overall findings strongly suggest that AD is an effective treatment for producing energy and good fertiliser, also reducing AB and ARG content as well as mitigating CH4 emissions into the atmosphere.